Molecular Analysis of Malassezia Microflora on the Skin of Atopic Dermatitis Patients and Healthy Subjects - Sugita, Takashi (American Society for Microbiology, 2001)
Members of the genus Malassezia, lipophilic yeasts, are considered to be one of the exacerbating factors in atopic dermatitis (AD). We examined variation in cutaneous colonization by Malassezia species in AD patients and compared it with variation in healthy subjects. Samples were collected by applying transparent dressings to the skin lesions of AD patients. DNA was extracted directly from the dressings and amplified in a specific nested PCR assay. Malassezia-specific DNA was detected in all samples obtained from 32 AD patients. In particular, Malassezia globosa and M. restricta were detected in approximately 90% of the AD patients and M. furfur and M. sympodialis were detected in approximately 40% of the cases. The detection rate was not dependent on the type of skin lesion. In healthy subjects, Malassezia DNA was detected in 78% of the samples, among which M. globosa, M. restricta, and M. sympodialis were detected at frequencies ranging from 44 to 61%, with M. furfur at 11%. The diversity of Malassezia species found in AD patients was greater (2.7 species detected in each individual) than that found in healthy subjects (1.8 species per individual). Our results suggest that M. furfur, M. globosa, M. restricta, and M. sympodialis are common inhabitants of the skin of both AD patients and healthy subjects, while the skin microflora of AD patients shows more diversity than that of healthy subjects. To our knowledge, this is the first report of the use of a nested PCR as an alternative to fungal culture for analysis of the distribution of cutaneous Malassezia spp.